Blood Lead Levels among Children in Yaoundé Cameroon - Monebenimp, Francisca; Kuepouo, Gilbert; Chelo, David; Anatole, Pieme Constant; Kany Bissek, Anne-Cécile Zoung; Gottesfeld, Perry (Frontiers in Public Health, 2017)
Blood lead levels (BLLs) are a useful indication of a population exposure to lead from environmental sources. No previous published study had reported BLLs in Cameroon. Our objective is to characterize exposure levels in children to inform policymakers of potential lead exposure sources. We tested the BLLs of 147 children aged 12 months to 6 years residing in Yaoundé, Cameroon, and conducted an extensive questionnaire with their parents or guardians to characterize potential exposure sources. The geometric mean BLL among this population was 8.0 μg/dl and arithmetic mean level was 8.7 μg/dl. These levels are more than sixfold higher than the geometric mean BLL reported in the U.S. and more than fivefold higher than those reported in France. In addition, 88% of the children tested had lead levels greater than 5 μg/dl. One limitation of the study is that the selection of the children sampled was not a random survey. The analysis of the responses to the questionnaire failed to uncover any specific exposure patterns. A statistically significant association was noted between the age of the child’s home and the duration of exclusive breastfeeding with BLLs. The study points to a need for greater efforts to control sources of lead exposure in Cameroon.